Comparison of microparticles produced with combinations of gelatin, chitosan and gum Arabic. (15th September 2018) - Gonçalves, Nathalia D.; Grosso, Carlos R.F.; Rabelo, Renata S.; Hubinger, Miriam D.; Prata, Ana S.
Highlights: Complex coacervation with three polymers was explored. High charge density of chitosan impacts complexation of gelatin and gum Arabic. Oil distribution in the particles depends on the polymer combination. Yield of polymer complexation changes in the presence of the oil. Abstract: The complexation between proteins and/or polysaccharides has been studied during decades and despite the knowledge of how these interactions occur provides a basis for identifying the conditions of microparticle formation, the presence of the oil phase complicates the application of available theory to explain the complexation between polymers. In this work, we identified some parameters which can interfere with this interaction, highlighting the influence of molecular arrangements by modifying the combination of gelatin (GE) and gum Arabic (GA) including the chitosan (CHI), a comparatively stronger polycation, to form particles in the presence or not of an essential oil. The results indicated the influence of the polymeric system in the morphological structure of particles as well as in the capacity of oil retention. The encapsulation of oil was more efficient for systems containing GA, due to the ability of these systems to form complexes. However, GE-GA particles presented as multinucleous while CHI-GA as a mononucleous structure.